2009
DOI: 10.1590/s1808-18512009000400012
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do efeito antinociceptivo do fentanil transdérmico no controle da dor lombar pós-operatória

Abstract: OBJETIVO: pacientes submetidos à laminectomia por via posterior geralmente reclamam de dor severa. A aplicação por via transdérmica de fentanil resulta em sua liberação contínua e poderia ser útil no controle da dor. Este estudo visou avaliar a eficácia do fentanil (F) transdérmico em dor aguda pós-operatória secundária à laminectomia por via posterior. MÉTODOS: após aprovação do Comitê de Ética em Pesquisa e consentimento adquirido, 24 pacientes foram distribuídos de forma aleatória e duplamente encoberta em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Recently, Minville et al [20] showed that TFP (50 μg/h for 24 h) decreases pain severity and rescue morphine consumption in patients undergoing total hip arthroplasty. Lauretti et al [15] reported that TFP (25 μg/h) provides a lower pain and lesser rescue analgesic consumption after posterior laminectomy. Also Barrera et al [3] assessed the safety and efficacy of TFP (50 μg/h) for postoperative analgesia in dorsal and lumbar spine arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Minville et al [20] showed that TFP (50 μg/h for 24 h) decreases pain severity and rescue morphine consumption in patients undergoing total hip arthroplasty. Lauretti et al [15] reported that TFP (25 μg/h) provides a lower pain and lesser rescue analgesic consumption after posterior laminectomy. Also Barrera et al [3] assessed the safety and efficacy of TFP (50 μg/h) for postoperative analgesia in dorsal and lumbar spine arthrodesis.…”
Section: Discussionmentioning
confidence: 99%